2017
DOI: 10.1002/wcms.1353
|View full text |Cite
|
Sign up to set email alerts
|

Growth control, interface behavior, band alignment, and potential device applications of 2D lateral heterostructures

Abstract: Two‐dimensional (2D) lateral heterostructures open a new avenue for intentional design of novel 2D devices with superior electronic and optoelectronic properties. Since 2012, many groups have successfully synthesized lateral graphene/h‐BN heterostructures on metal substrates and the fabrication of in‐plane heterostructures of transition metal dichalcogenides has also been reported since 2014. In this review, we first present an overview on recent progress of the experimental fabrications of 2D lateral heterost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 102 publications
(224 reference statements)
1
33
0
Order By: Relevance
“…Theoretical calculations were conducted to probe the whole growth process of the G-h-BN heterostructures. It was previously reported that hexagonal G crystals grown on metal substrates have zigzag (ZZ) edges 18 ; since several experiments confirmed a ZZ edge at the interface of G and h-BN in-plane heterostructures 9,24 , it was assumed that in our case, the subsequent h-BN growth would be atomically grown along the ZZ edges of the G. Furthermore, it was shown that two bonded modes exist when h-BN is atomically connected with graphene, where one is a C-N bond and the other is a C-B bond 25 . In our case, the interface between the G flake and h-BN periphery was also investigated.…”
Section: S3-s5mentioning
confidence: 71%
“…Theoretical calculations were conducted to probe the whole growth process of the G-h-BN heterostructures. It was previously reported that hexagonal G crystals grown on metal substrates have zigzag (ZZ) edges 18 ; since several experiments confirmed a ZZ edge at the interface of G and h-BN in-plane heterostructures 9,24 , it was assumed that in our case, the subsequent h-BN growth would be atomically grown along the ZZ edges of the G. Furthermore, it was shown that two bonded modes exist when h-BN is atomically connected with graphene, where one is a C-N bond and the other is a C-B bond 25 . In our case, the interface between the G flake and h-BN periphery was also investigated.…”
Section: S3-s5mentioning
confidence: 71%
“…To the best of our knowledge, until now, such heterostructures have been obtained, on the one hand, only between graphene and h‐BN since 2012 [ 32–34 ] and with transition metal dichalcogenides since 2014, on the other hand. [ 8 ] These novel heterostructures will further boost fundamental studies, not only in electronics, but also, typically, in spintronics and optoelectronics. [ 37 ] Progress in engineering, for example, to tailor nanoribbons and lateral superlattices, and use such effects as negative differential resistance, can be anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Besides lateral graphene/h‐BN heterostructures, fabrication of several in‐plane heterostructures of transition metal dichalcogenides has also been reported. [ 8 ] Very recently, vertical heterostructures have been prepared by boron intercalation underneath graphene, while, more strikingly, lateral integration of borophene with graphene has been realized. [ 9 ] At variance, there is no experimental report of the realization of such monolayer in‐plane heterostructures for the group 14 post‐graphene 2D materials, although each of them typically possesses very high hole and electron mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, in‐plane heterostructures of 2D TMDCs were first identified by the one‐step or two‐step chemical vapor deposition (CVD) method, which permits modification of the atomic composition of a single monolayer to manifest in‐plane heterostructures . In‐plane heterostructures of 2D TMDCs, such as MoS 2 /WS 2 , MoSe 2 /WSe 2 , MoS 2 /MoSe 2 as wells as MoS 2 /WSe 2 mark the ultimate thickness limit for junctions between semiconducting materials.…”
Section: Photoexcitation Dynamics Of Chargr Carriersmentioning
confidence: 99%